2002
DOI: 10.1002/jso.10104
|View full text |Cite
|
Sign up to set email alerts
|

Desmoid tumors: A novel approach for local control

Abstract: For potentially resectable lesions, this protocol provides excellent local control, even in those with recurrent disease. Neoadjuvant treatment with doxorubicin and radiotherapy appears to be a better option than surgery alone, or surgery and adjuvant radiotherapy. These results need to be confirmed in larger, prospective randomized trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
8

Year Published

2004
2004
2008
2008

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 17 publications
1
27
0
8
Order By: Relevance
“…Traditionally, desmoid tumours have been managed with surgery with wide local excision being the preferred treatment [3,10,16,19]. Over the past 10 years, adjuvant therapy, employing radiation therapy, chemotherapy, anti-estrogenic agents such as tamoxifen and even NSAIDs have been used in an attempt to reduce the risk of local recurrence [1,11,14]. Despite various studies, the natural history of these tumours remains enigmatic, with paucity of information on the optimal treatment protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, desmoid tumours have been managed with surgery with wide local excision being the preferred treatment [3,10,16,19]. Over the past 10 years, adjuvant therapy, employing radiation therapy, chemotherapy, anti-estrogenic agents such as tamoxifen and even NSAIDs have been used in an attempt to reduce the risk of local recurrence [1,11,14]. Despite various studies, the natural history of these tumours remains enigmatic, with paucity of information on the optimal treatment protocol.…”
Section: Introductionmentioning
confidence: 99%
“…Five year local recurence rates of 8 to 44% were reported by other series, and was 36% in the present study (2,34,110,114,115,137,182,184). Most recurrences are usually observed within 3 years, and nearly all by 6 years and m ost of the studies found that the presence of positive surgical margin proved to be relevant in patients with recurrent disease (19,34,110,114,115,137,(182)(183)(184). Well corresponding with these results, the median time to recurrence in our series was 26 months (range 6-110 months) and the investigator established that obtaining a wide disease-free margin is crucial for reducing the recurrence rate.…”
Section: Sporadical Desmoid Tumors Of the Abdominal Wallsupporting
confidence: 66%
“…Due to the lack of randomized, controlled trials, we have tried to extrapolate from the published series those cases with tumors localized to the abdominal wall to compare with our findings (2,19,34,110,114,115,137,(182)(183)(184). Table 22.…”
Section: Sporadical Desmoid Tumors Of the Abdominal Wallmentioning
confidence: 95%
“…A Tri-Center Study confirmed local control rates of 98.5% [6]. Furthermore, the same approach to desmoid tumors yields an 85% 5-year local control rate [7]. This is despite desmoid tumors having notoriously high local recurrence rates ranging from 18 to 56% [8][9][10].…”
Section: Discussionmentioning
confidence: 93%